Creative Cities and Knowledge Management Approach to Culture-Based Urban Regeneration in Slovakia: A Model - Mária Tajtáková; Mária Olejárová (Communications - Scientific letters of the University of Zilina, 2021)
The term "Creative City" emerged in the 90s of the 20th century reflecting the trend of transforming post-industrial cities into new creative urban centres - bases for knowledge intensive firms, highly-skilled workers and major cultural assets. The concept of culture-based urban regeneration describes a scheme where culture is purposely employed as a vehicle for an overall urban and social revitalization. The paper addresses innovative processes within culture-based urban regeneration projects in three Slovak cities - Bratislava, Zilina and Kosice - under the concept of creative city. The focus is on the implementation of a tailor-made multi-factor knowledge management model with the aim of exploring the knowledge management practices in urban development projects dealing with the adaptive re-use of industrial and cultural heritage based on the non-profit bottom-up initiatives.